The value of urinalysis in presumptive diagnosis of urinary tract infection in children - Dedi Rachmadi; Andaningrum Setyastuti (Indonesian Pediatric Society, 2008)
Background Definite diagnosis of urinary tract infection (UTI)should only be established based on culture of urine specimen,otherwise it would be considered presumptive. Since urinalysisprovides more rapid information than urine culture, cliniciansshould consider to utilize urinalysis as a decision-making tool forinitiating treatment of UTI.Objective To determine the sensitivity, specificity, predictive val-ues, and accuracy of several urinalysis parameters, namely the ni-trite, leukocyte esterase (LE), Gram staining, and methylene bluereductase (MBR) tests, in supporting the diagnosis of UTI.Methods This diagnostic test was done on 30 subjects with pyuriaduring the period of April to June 2004. The sensitivity, specific-ity, positive predictive value (PPV), negative predicitve value(NPV) as well as the accuracy were calculated for each urinalysisparameter with urine culture as the gold standard. The relation-ship between categorical variables was analyzed by Fisher's exacttest or chi square test.Results The sensitivity, specificity, PPV, NPV and accuracy fornitrite test, leukocyte esterase (LE) test, Gram staining, and MBRtest were respectively as follows: nitrite test showed 90.5%, 66. 7%,86.4%, 75%, and 83.3%; LE test yielded 95.2%, 33.3%, 76.9%,75%, and 76.4%; Gram staininglOO%, 44.4%, 80.8%, 100%, and83.3%; and MBR test 85.7%, 100%, 100%, 75%, and 90%.Conclusions The MBR, among other urinalysis routine tests, hasthe highest specificity and accuracy as well as high sensitivity inestablishing a presumptive diagnosis of UTI